Oxytocin at Elective Cesarean Delivery: A Dose-finding Study in Women With Obesity. Issue 2 (24th June 2022) - Peska, E.; Balki, M.; Maxwell, C.; Ye, X.Y.; Downey, K.; Carvalho, J.C.A.
Abstract : ( Anaesthesia . 2021;76:918–923. [Epub November 23, 2020]) Worldwide, postpartum hemorrhage (PPH) continues to be a major cause of maternal mortality. Uterine atony is a leading cause of PPH in high-income countries and is known to be associated with obesity. Oxytocin is administered to achieve acceptable uterine tone following cesarean delivery (CD); however, it is unknown whether higher doses of oxytocin are required to accomplish this in women with obesity. This dose-finding study examined the oxytocin bolus dose required to initiate effective uterine tone in 90% of women with obesity (ED90 ) following CD under regional anesthesia.